Training using virtual reality improves response behavior in karate kumite - Petri, K.; Emmermacher, P.; Danneberg, M.; Masik, S.; Eckardt, F.; Weichelt, S.; Bandow, N.; Witte, K. (Sports Engineering, 2019)
The aim was to study if sports-specific reaction training using immersive virtual reality improves the response behavior of karate athletes. During ten sessions, 15 experienced young karate athletes responded to upcoming attacks of a virtual opponent. On one hand, in PRE and POST tests, we examined the sports-specific response behavior using the time for response (time between a defined starting point and the first reaction), response accuracy (according to a score system), and kind of response (direct attack or a blocking movement) based on a movement analysis. On the other hand, we analyzed the unspecific response behavior using the reaction time and motor response time based on the reaction test of the Vienna test system. Friedman tests with subsequent Dunn-Bonferroni post-hoc tests and one-factorial ANOVAs showed no significant differences (p > 0.05) in the unspecific parameters. However, significant improvements (p < 0.05) of the sports-specific parameters were found, leading to a higher increase within the intervention groups (large effects) compared to the control groups (small and moderate effects in time for response, and no significant effects in response quality). It can be concluded that VR training is useful to improve response behavior in young karate athletes.